Filovirus VP24 Proteins Differentially Regulate RIG-I and MDA5-Dependent Type I and III Interferon Promoter Activation - He, Felix B.; Khan, Hira; Huttunen, Moona; Kolehmainen, Pekka; Melén, Krister; Maljanen, Sari; Qu, Mengmeng; Jiang, Miao; Kakkola, Laura; Julkunen, Ilkka (Frontiers in Immunology, 2022)
Filovirus family consists of highly pathogenic viruses that have caused fatal outbreaks especially in many African countries. Previously, research focus has been on Ebola, Sudan and Marburg viruses leaving other filoviruses less well studied. Filoviruses, in general, pose a significant global threat since they are highly virulent and potentially transmissible between humans causing sporadic infections and local or widespread epidemics. Filoviruses have the ability to downregulate innate immunity, and especially viral protein 24 (VP24), VP35 and VP40 have variably been shown to interfere with interferon (IFN) gene expression and signaling. Here we systematically analyzed the ability of VP24 proteins of nine filovirus family members to interfere with retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated antigen 5 (MDA5) induced IFN-beta and IFN-lambda1 promoter activation. All VP24 proteins were localized both in the cell cytoplasm and nucleus in variable amounts. VP24 proteins of Zaire and Sudan ebolaviruses, Lloviu, Taï Forest, Reston, Marburg and Bundibugyo viruses (EBOV, SUDV, LLOV, TAFV, RESTV, MARV and BDBV, respectively) were found to inhibit both RIG-I and MDA5 stimulated IFN-beta and IFN-λ1 promoter activation. The inhibition takes place downstream of interferon regulatory factor 3 phosphorylation suggesting the inhibition to occur in the nucleus. VP24 proteins of Mengla (MLAV) or Bombali viruses (BOMV) did not inhibit IFN-beta or IFN-λ1 promoter activation. Six ebolavirus VP24s and Lloviu VP24 bound tightly, whereas MARV and MLAV VP24s bound weakly, to importin alpha5, the subtype that regulates the nuclear import of STAT complexes. MARV and MLAV VP24 binding to importin alpha5 was very weak. Our data provides new information on the innate immune inhibitory mechanisms of filovirus VP24 proteins, which may contribute to the pathogenesis of filovirus infections.